2000
DOI: 10.2172/766758
|View full text |Cite
|
Sign up to set email alerts
|

Source Document: The Relationship Between Pocket Gophers (Thomomys bottae) and the Distribution of Buried Radioactive Waste at the Los Alamos National Laboratory

Abstract: Material Disposal Area G at the Los Alamos National Laboratory is a lowlevel radioactive waste storage facility. The noticeable presence of pocket gopher mounds and cast soil on closed waste burial sites of various types resulted in the need to understand possible interactions between gophers and radioactive waste at Area G. In our study, pocket gophers, mound soil, off-mound surface soil, and vegetation were collected at Area G and at off-site background locations. The samples were analyzed for 241 Am, 238 Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The general inhalation ESL model used for burrowing mammals was modified from Carlsen [1] and is ESL ϭ (BW·TRV/IR)·OF (1) where ESL is the ecological screening level (mg/m 3 ); BW is the ecological receptor body weight (kg); TRV is the VOC toxicity reference value (mg/kg/d); IR is the ecological receptor inhalation rate (m 3 /d); OF is the occupancy factor, the fraction of time the ecological receptor spends in the burrow (unitless). Several conservative exposure assumptions were used in calculating ESLs, such as the use of the lowest adult body weight [12] for the ecological receptor to result in a maximum weight-adjusted inhalation rate, as well as use of the maximum body weight in TRV derivation to yield the lowest TRV. In addition, an occupancy factor of 1 for the ecological receptor is used to represent 100% occupancy, or all of its time in the burrow, for maximum exposure time.…”
Section: Inhalation Esl Calculationmentioning
confidence: 99%
“…The general inhalation ESL model used for burrowing mammals was modified from Carlsen [1] and is ESL ϭ (BW·TRV/IR)·OF (1) where ESL is the ecological screening level (mg/m 3 ); BW is the ecological receptor body weight (kg); TRV is the VOC toxicity reference value (mg/kg/d); IR is the ecological receptor inhalation rate (m 3 /d); OF is the occupancy factor, the fraction of time the ecological receptor spends in the burrow (unitless). Several conservative exposure assumptions were used in calculating ESLs, such as the use of the lowest adult body weight [12] for the ecological receptor to result in a maximum weight-adjusted inhalation rate, as well as use of the maximum body weight in TRV derivation to yield the lowest TRV. In addition, an occupancy factor of 1 for the ecological receptor is used to represent 100% occupancy, or all of its time in the burrow, for maximum exposure time.…”
Section: Inhalation Esl Calculationmentioning
confidence: 99%
“…[11] Two types of soil samples were collected at each study site, including at the reference sites. [11] Two types of soil samples were collected at each study site, including at the reference sites.…”
Section: Sample Collectionmentioning
confidence: 99%
“…The pocket gophers occupying the area within the study site were identified as Thomomys bottae, or western pocket gopher. [11] MATERIALS AND METHODS The burrow system of pocket gophers usually consists of a relatively shallow main tunnel with many branching side tunnels that are used for foraging, and a deeper tunnel system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increased interest in estimating doses to non-human biota that arise from radiological releases into the environment to evaluate the impacts to environmental resources (Gonzales et al 2000, Ferenbaugh et al 2002. The Laboratory, in 1998, developed an ecological risk assessment model for application to evaluating radiological doses in LANL's corrective action program (Environmental Restoration Project 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transuranic wastes have been stored on pads in the northeast portion of the site. As part of the Laboratory's Environmental Surveillance Program, the Ecology Group has sampled media at Area G, including soils/sediments (Fresquez et al , 1999Nyhan et al 2000Nyhan et al , 2001, vegetation (Fresquez et al , 1999Nyhan et al 2000Nyhan et al , 2001, and small mammals (Biggs et al , 1997 Area G Gonzales et al 2000). These sampling and analytical activities have revealed elevated levels of several radionuclides in these media.…”
Section: Introductionmentioning
confidence: 99%